2016
DOI: 10.1097/md.0000000000004365
|View full text |Cite
|
Sign up to set email alerts
|

Variations of movement disorders in anti-N-methyl-D-aspartate receptor encephalitis

Abstract: Anti-N-methyl-d-aspartate receptor (NMDAR) encephalitis is one of the most common autoimmune encephalitis that presents with a wide variety of movement disorders. The purpose of our study is to review the manifestations and duration of movement disorders in different ages with NMDAR encephalitis.A retrospective cohort of 28 patients (20 females and 8 males) with positive cerebrospinal fluid (CSF) anti-NMDAR antibody in a 5-year period from major hospitals in Taiwan was enrolled. They were categorized into 3 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 35 publications
(62 reference statements)
1
25
0
Order By: Relevance
“…With regard to the overall clinical manifestations during HSV‐induced anti‐NMDAR encephalitis, our literature review shows that the clinical picture is similar to that of anti‐NMDAR encephalitis not preceded by HSE, including the known age‐specific features of the disease. Indeed, psychiatric symptoms were more frequent in adults in our literature cohort, whereas neurological manifestations, such as movement disorder, were more represented in children (Table SI), similarly to what was previously reported in patients with anti‐NMDAR encephalitis not preceded by HSE . Although it should be taken into account that under‐reporting of psychiatry and cognitive features in young children is possible, we also observed a slightly more severe disease in children than in adults, and a shorter latency between HSE and autoimmune encephalitis in children.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With regard to the overall clinical manifestations during HSV‐induced anti‐NMDAR encephalitis, our literature review shows that the clinical picture is similar to that of anti‐NMDAR encephalitis not preceded by HSE, including the known age‐specific features of the disease. Indeed, psychiatric symptoms were more frequent in adults in our literature cohort, whereas neurological manifestations, such as movement disorder, were more represented in children (Table SI), similarly to what was previously reported in patients with anti‐NMDAR encephalitis not preceded by HSE . Although it should be taken into account that under‐reporting of psychiatry and cognitive features in young children is possible, we also observed a slightly more severe disease in children than in adults, and a shorter latency between HSE and autoimmune encephalitis in children.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, psychiatric symptoms were more frequent in adults in our literature cohort, whereas neurological manifestations, such as movement disorder, were more represented in children (Table SI), similarly to what was previously reported in patients with anti-NMDAR encephalitis not preceded by HSE. 11,45,46 Although it should be taken into account that under-reporting of psychiatry and cognitive features in young children is possible, we also observed a slightly more severe disease in children than in adults, and a shorter latency between HSE and autoimmune encephalitis in children.…”
Section: Clinical Features Of Hsv-induced Anti-nmdar Encephalitismentioning
confidence: 59%
“…Studies have shown that children tend to have neurological symptoms more frequently 82 as opposed to psychiatric ones, and appear to have a higher incidence of movement disorders, with numbers of children noted to have a movement disorder ranging from 60% 83 to 90%, 84,85 which included unilateral dystonia, speech disturbance, status epilepticus, 78 and gait disturbances. 86 Granata et al 87 compared the movement disorders in children and teenagers (>12 years of age) with anti-NMDAr encephalitis and found that catatonic symptoms were much more prevalent in adolescents than in children, as other studies 88 had shown before. In children, especially those under 12, behavioral changes may present themselves with increased temper tantrums, hyperactivity, or irritability as opposed to frank psychosis.…”
Section: Encephalitismentioning
confidence: 92%
“…The most common MD reported in literature is orofacial lingual dyskinesia (OFLD), which is characterized by perioral grimacing, chewing, tongue thrusting, lip smacking, and frowning movements. In a series of 28 patients of NMDAR antibody‐positive encephalitis reported by Duan et al, OFLD (20/28) was the most common MDs followed by catatonia (n = 19), tremor (n = 11), bradykinesia (n = 11), dystonia (n = 11), choreoathetosis (n = 9), and ballism (n = 3) . The pathogenesis of this form of movement could be due to the hypersensitivity of the dopaminergic system, the instability between dopamine and cholinergic systems, and impairments of striato‐nigral GABAergic neurons.…”
Section: Search Resultsmentioning
confidence: 98%